Experimental and molecular dynamics investigations of the effects of ionic surfactants on the wettability of low-rank coal - Gan, Jian (2023)
The wetting properties of ALES (Ammonium lauryl ether sulfate), SLES (sodium lauryl ether sulfate), TD (dodecyl triethanolamine salfate) and SDS (sodium dodecyl sulfate) solutions and their adsorption capacities on coal dust surface were evaluated by surface tension, contact angle, sink time, wetting rate, and changes in the micromorphology and functional groups on coal surface. The results showed that the four surfactants share similar adhesion and spreading wettability, while they differ notably in immersion wetting. A water-surfactant-low rank coal (LRC) system was established using Materials Studio software and the Wender coal model; then quantum chemical calculations and molecular dynamics (MD) simulations were conducted. The results showed that ALES is of the widest relative concentration distribution range (25.25–60 Å), the largest overlap range (25 Å) and the largest diffusion coefficient (D = 0.318); NH4+ can easily penetrate the surfactant layer, which proves the strong modification ability of ALES to LRC. ALES/LRC/H2O has the lowest interaction energy and the most H-bonds, indicating that ALES is of a strong adsorption capacity. Based on the experimental data and simulation results, the integrated wettabilities of the four surfactants follow ALES＞SLES＞TD＞SDS, partially contributed by the hydrolytic cations and EO groups.